Advances and emerging research trends in maritime transport logistics: environment, port competitiveness and foreign trade - Paola Alzate; Gustavo A. Isaza; Eliana M. Toro; Jorge A. Jaramillo-Garzón (International Journal of Production Management and Engineering)
The operations of international trade drive global economies, with maritime transport serving as a key pillar in market connectivity and acceleration. The opportunities presented by Industry 4.0 to connect supply chain actors through integrated logistics pose a challenge that fuels the number of studies in this area, with a particular interest in the transportation stage due to its responsibilities for efficiency. This study conducts a systematic literature review by analyzing scientometric aspects and identifying research trends related to maritime transportation logistics. The PRISMA methodology, graph theory, and bibliometric indicators such as indegree, betweenness, and outdegree were employed to process the information related to maritime transportation logistics from the Scopus and Web of Science databases spanning from 2000 to 2022. The gathered information and results were processed and analyzed using R-studio and Bibliometrix tools. The documents were classified as original, structural, and research trends, with the latter focused on topics related to the environment, port competitiveness, logistics optimization, and economics. Finally, an agenda for future research in the field is presented.